Tinjauan Material Umpan Pancing Ikan Artifisial - Bernando, Ardo (ArtComm, 2024)
This article reviews the variety of artificial fishing bait materials as a continuation of the author's previous study on the biomimicry review of the shape of artificial fishing bait. The study is based on the understanding that the role of materials in the design of man-made products plays an important role as aspects of form and also aspects of function. The purpose of this study is to find out what and how the various types of artificial fishing bait materials are usually used at the large industrial level or UMKM, and to map them so that they can become general knowledge and references in designing. Data collection was carried out by direct exploration and also through internet browsing with samples that were considered representative for discussion, while the data discussion method used a qualitative discussion style that was descriptive and illustrative, equipped with supporting image explanations. The results of the review show that almost all materials can be made as artificial fishing bait, both raw materials from nature or those that have been processed. Further research is needed to find out what and how the various functions of artificial fishing bait are and their relationship to aspects of form and material aspects.